NFLUENCE OF SALTED ENVIRONMENT ON FODDER HERBS EFFICIENCY OF PASTURABLE PHYTOCOENOSES OF THE NORTH-WESTERN CASPIAN LOWLAND - R. Z. Usmanov; M. A. Babaeva; S. V. Osipova (Юг России: экология, развитие, 2014)
Abstract. The changes in the intensity of biological processes in the vegetation and productivity of forage grasses depending on the degree of soil salinity of the North-West Caspian Lowland were studied. Salination factors are specific. They are formed because of their adaptive nature, providing for species the opportunity to get the certain position in the relevant biocenosis. As a result each species produces its own strategy of life. Development of saline processes of soil in the growth and development of the plant mass, biological and agronomic salt resistance is clearly seen. Biological salt resistance is characterized by the ability to maintain the viability of the plant body at the upper limit of salinity. Agronomical salt resistance is determined by the value of crop and productivity. Adaptive possibilities of different plant species with different biological characteristics were also examined.Subject, objective of the work. Productivity of vegetation of semidesert ecosystems and dynamics under the influence of salinity forage grass pasture phytocenoses of the North-West Caspian Lowland were studied.Test method. We studied fodder crops: wheat grass long (Elytrigia elongata), ctenoid wheatgrass (Agropirum cristatum) and alfalfa (Medicago sativa). The crop from each significant area was weighed; it was taken from the average sample weighed in at 1 kg in a gauze bag for drying at a temperature of 60–65 °C in airing cupboard where brought to constant weight. Accounting for phytomass was carried by laying mowing area 8–10 times. Dimensions of mowing fields are 0.25 m2, that ensured coverage of all dominant plants.Results. At mid-saline meadow-chestnut soil of the North-West Caspian Lowland wheatgrass long gives the highest yield of green mass – 18,1 tons per hectare of dry weight average for 2003–2010. Alfalfa crop is in the second place, that is less than bluegrass by 18.0 % (2.9 tons per hectare). The least yield of these crops is ctenoid wheatgrass, which is less than other grasses by 4.8 tons per hectare (26.1 %) and 1.7 tons per hectare (11.3 %). Therefore, wheatgrass long is hardier to mid-saline soil than other species. High yield of alfalfa depends on frequent mowing of this grass. In the sowing year there were three hay crops, the second and subsequent years - 4 mowing. The share of the first mowing in the sowing year alfalfa has 33.0 %, the second 42.3 %, the third 24.7 %. In the second and subsequent years the share of the first mowing in the total yield of green mass increases up to 28,3–28,8, the third to 19,0–20,6, the fourth to 8,8–10,7 %.Area of application. The research results can be used by the economic organizations and enterprises for the phytomelioration of saline soils. The obtained data can be used to enhance and achieve high productivity of forage grasses and to restore the productivity of saline lands and use them for agricultural purposes.Conclusions. Adaptability to the saline soil and the productivity of forage grasses differ according to biological characteristics and extent soil salinity and ecological conditions.